1, 3‐Dipolar Cycloaddition of Imidazole Derivatives with Nitrile Oxide: Synthesis of Imidazo[1, 2, 4]oxadiazole Derivatives. Issue 11 (16th August 2017) - Jiang, Kun‐Ming; Zhang, Jian‐Qiang; Jin, Yi; Lin, Jun
Abstract: A concise and efficient synthesis of imidazo[1, 2, 4]oxadiazole derivatives that proceeds through the [3+2] cycloaddition of 2‐chloro‐1 H ‐benzo[ d ]imidazole with nitrile oxides has been developed. This strategy can conveniently construct tricyclic imidazole heterocyclic derivatives that contain a broad range of functional groups. Compound3 p showed excellent cytotoxic activity against the KYSE410 cell line (IC50 =0.26 μm ). These tricyclic imidazole heterocyclic derivatives are promising candidates for drug discovery. Abstract : Polar express : A concise and efficient synthesis of imidazo[1, 2, 4]oxadiazole derivatives that proceeds through the [3+2] cycloaddition of 2‐chloro‐1 H ‐benzo[d]imidazole with nitrile oxides has been developed. This strategy can be used to conveniently construct tricyclic imidazole heterocyclic derivatives that have a broad range of functional groups. Compound3 p showed excellent cytotoxic activity against the KYSE410 cell line (IC50 =0.26 μm ).